Algoritma FP-Growth untuk Menganalisa Frekuensi Pembelian Gas Elpiji 3 Kg - Elisa, Erlin; Azwanti, Nurul (Universitas Nusantara PGRI Kediri, 2019)
The use of gas in Indonesia is a more profitable alternative, one of which is the oil conversion program, LPG (liquefied petroleum gas). UD.Maju Bersama, which is a distribution agent for 3 Kg LPG gas for household needs, so far because of the many requests, of course LPG agents like this need to forecast the frequency of purchases to find out if the sales have been sold as optimally as possible and stocks can be provided well and supplies adequate for consumer demand. this problem can be solved by applying one of the Datamining techniques which is using the FP-Growth Algorithm method to find out the Frequency of Purchase of 3 Kg LPG Gas. Frequent Pattern Growth (FP-Growth) can be used to determine the set of data that most often appears (frequent itemset) in a data set. The results of data processing purchases at the Elpiji UD base. Forward Together the most sold or purchased values ​​at week 1 and 2 on each month with the highest value support 66.67% confidence 100.00%. the results can help base owners to make decisions on gas supply so that they can be used to increase the amount of supply from distributors to agents and increase profits with support and confidence.